Evaluation of Williamson–Hall Strain and Stress Distribution in ZnO Nanowires Prepared Using Aliphatic Alcohol - Thandavan, T.M.K.; Gani, S.M.A.; Wong, C.S.; Nor, R.M. (Kluwer (now part of Springer), 2015)
Synthesis of ZnO nanowires (NWs) using vapor phase transport (VPT) assisted with thermal evaporation of brass (CuZn) assisted by hotwire was presented. The effects of aliphatic alcohols such as methanol and ethanol as source of oxygen were investigated using field emission scanning electron microscope and X-ray diffraction (XRD). Significant changes in the morphology and structure of both ZnO NWs prepared using methanol (ZnO/M NWs) and ethanol (ZnO/E NWs) depicted the influence of aliphatic alcohols. Debye Scherer (DS), Williamson–Hall (W-H) and size–strain plot (SSP) analysis on the XRD peak broadening revealed that ZnO/M NWs revealed lower strain and stress value compared to ZnO/E NWs. ZnO/M NWs, which was preferential to $$\langle 002\rangle $$⟨002⟩ crystallographic orientation found to be hexagonal isotropic crystalline nature whereas ZnO/E NWs preferential of $$\langle 101\rangle $$⟨101⟩ crystallographic orientation is anisotropic crystalline nature.